1994
DOI: 10.2307/3578738
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Radiation-Induced Damage to Spermatogenesis by Hormone Treatment

Abstract: Infertility caused by killing of the spermatogonial stem cells occurs frequently in men treated for cancer with radiotherapy and chemotherapy. We investigated whether pretreatment of rats with testosterone plus estradiol, which reversibly inhibits the completion of spermatogenesis and protects spermatogonial stem cells from procarbazine-induced damage, would also protect these cells from radiation. Adult male LBNF1 rats were implanted for 6 weeks with capsules containing testosterone and estradiol and then irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 22 publications
1
17
0
2
Order By: Relevance
“…The mechanism behind the secondary decline is not known, but our recent results suggest that the mechanism may be under endocrine regulation and can be manipulated by hormone treatment. In LBNF 1 rats, suppression of LH and intratesticular testosterone levels by testosterone plus estradiol treatment prior to irradiation markedly improved recovery of spermatogenesis at 10 wk following a single 3.5-Gy dose of irradiation [13]. We propose that hormone treatment affected the recovery from stem cells after irradiation.…”
Section: Recovery Of Spermatogenesismentioning
confidence: 82%
See 1 more Smart Citation
“…The mechanism behind the secondary decline is not known, but our recent results suggest that the mechanism may be under endocrine regulation and can be manipulated by hormone treatment. In LBNF 1 rats, suppression of LH and intratesticular testosterone levels by testosterone plus estradiol treatment prior to irradiation markedly improved recovery of spermatogenesis at 10 wk following a single 3.5-Gy dose of irradiation [13]. We propose that hormone treatment affected the recovery from stem cells after irradiation.…”
Section: Recovery Of Spermatogenesismentioning
confidence: 82%
“…In contrast to Sprague-Dawley rats, in which more than 95% of tubules show repopulation after doses of [3][4] in LBNF, rats only 12% of tubules recover after 3 Gy [13]. Similarly, after treatment with procarbazine, another agent known to kill stem spermatogonia, LBNF, rats show poorer recovery of spermatogenesis than do Sprague-Dawley rats [14].…”
Section: Introductionmentioning
confidence: 95%
“…In each preparation, at least 200 sperm was counted. This motility assessment was repeated in a new preparation from the same semen sample (Kurdoglu et al, 1994).…”
Section: Sperm Parameters Assessmentmentioning
confidence: 99%
“…Increased stem cell survival was evident by 50 days, and at 90 days sperm count was close to normal and significantly higher than it was in rats treated with procarbazine alone. Similar protective effects of hormonal treatment have been described following the use of testosterone [37], testosterone and estradiol [38], GnRH and testosterone [39], and GnRH and the antiandrogen flutamide [40,41], following gonadal insult with procarbazine, cyclophosphamide, or radiotherapy. Pogach et al [39] suggested that testosterone administered after treatment with procarbazine enhanced the recovery of spermatogenesis.…”
Section: Hormonal Manipulationmentioning
confidence: 63%